2015
DOI: 10.11613/bm.2015.011
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma vaspin concentration in patients with sepsis: an exploratory examination

Abstract: IntroductionVaspin (visceral adipose tissue-derived serpin) was first described as an insulin-sensitizing adipose tissue hormone. Recently its anti-inflammatory function has been demonstrated. Since no appropriate data is available yet, we sought to investigate the plasma concentrations of vaspin in sepsis.Materials and methods57 patients in intensive care, fulfilling the ACCP/SCCM criteria for sepsis, were prospectively included in our exploratory study. The control group consisted of 48 critically ill patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
(27 reference statements)
2
5
0
Order By: Relevance
“…Similarly to our study, in the first examination in adult patients with sepsis increased plasma vaspin concentration was demonstrated [30]. The authors noted a weak positive correlation between vaspin and CRP concentration [30]. Moreover, such stated other authors, this adipokine significantly correlated with high CRP values in obese children with metabolic syndrome, in whom higher vaspin concentrations were noted, than in children without this pathology [21].…”
Section: Mode Of Deliverysupporting
confidence: 87%
See 2 more Smart Citations
“…Similarly to our study, in the first examination in adult patients with sepsis increased plasma vaspin concentration was demonstrated [30]. The authors noted a weak positive correlation between vaspin and CRP concentration [30]. Moreover, such stated other authors, this adipokine significantly correlated with high CRP values in obese children with metabolic syndrome, in whom higher vaspin concentrations were noted, than in children without this pathology [21].…”
Section: Mode Of Deliverysupporting
confidence: 87%
“…The study was limited by the low numbers of early-onset infected neonates, but in the future, assessment of SVC may be a new useful biomarker of these infections. Similarly to our study, in the first examination in adult patients with sepsis increased plasma vaspin concentration was demonstrated [30]. The authors noted a weak positive correlation between vaspin and CRP concentration [30].…”
Section: Mode Of Deliverysupporting
confidence: 86%
See 1 more Smart Citation
“…The investigators also demonstrated a weak positive correlation between the concentration of vaspin and CRP (r = 0.31, P = 0.002). Although there seems to be some relationship between vaspin and inflammation, its role in human sepsis needs to be evaluated further (53). …”
Section: Clinical Chemistrymentioning
confidence: 99%
“…The peptidoglycan (PGN) recognition protein 1 (PGLYRP1) as a ligand for TREM-1, a known proin-flammatory receptor expressed on monocytes/macrophages and neutrophils [25]. Vaspin, a visceral adipose tissue-derived serpin, was first identified as an insulinsensitizing adipose tissue hormone, and its antiinflammatory function has recently been demonstrated a weak positive correlation between the concentration of vaspin and CRP [26]. A recent study showed that using a panel of biomarkers consisting of angiopoietin-1, angiopoietin-2, and bicarbonate was a better predictor of severity in pediatric septic patients [27].…”
Section: Experimental Analytesmentioning
confidence: 99%